Pengembangan Board Game untuk Meningkatkan Minat Belajar Siswa Kelas IV SD - Nurfaizah, Nadia; Maksum, Arifin; Wardhani, Prayuningtyas Angger (Jurnal PGSD, 2021)
Board games can be used as learning media to help the Civics learning process on the meaning of the relationship between the symbols and the Pancasila precepts in Theme 4 (various jobs). The purpose of this study was to produce game-based learning media in order to increase the learning interest of fourth grade students towards the content of Civics subjects. This research is a development research with a modified ADDIE development model. This development model consists of stages of analysis, design, development, implementation and evaluation. This stage in research and development is carried out until the development stage. The instrument used in this study was a questionnaire to analyze the needs of teachers and students as well as a validation instrument for experts. Data collection techniques using quantitative and qualitative data. The results of the study indicate that the board game media is suitable for use in Civics subjects for grade IV SD with reference to the results of expert validation. The results of media expert validation are 74% or Valid. The results of validation by linguists obtained a percentage of 80% or Valid.